Determinants of Budget Balance in Local Government in the Process of Achieving Fiscal Sustainability - Evidence from Poland - Paweł GALIŃSKI (Communications of International Proceedings, 2021)
The study presents the determinants of budget balance in local government as factors affecting fiscal sustainability. First and foremost, the idea of fiscal sustainability and the impact of budget deficit on this phenomenon were characterized. Furthermore, some determinants of budget balance were studied by means of the results of the regression analysis for local government sector in Poland. The analysis concerns the period 1996-2019, in which factors in the field of finance, election cycle as well as the influence of the financial crisis of 2007 were involved. Therefore, the results of the findings should contribute to the proper budget policy aimed at ensuring fiscal sustainability in the public sector.
Keywords: Local government; budget balance; fiscal sustainability; fiscal situation.